In vitro Activities of Nemonoxacin and Other Antimicrobial Agents Against Human Mycoplasma and Ureaplasmas Isolates and Their Defined Resistance Mechanisms - Wang, Na; Liu, Wancheng; Zhou, Yunheng; Liu, Yang (Frontiers in Microbiology, 2019)
Nemonoxacin, a newly developed non-fluorinated quinolone (NFQ), selectively inhibits bacterial DNA topoisomerase activity. However, its activities against Mycoplasmas have rarely been studied to date. Herein, the activities of nemonoxacin were evaluated against clinical isolates of 50 Mycoplasma pneumoniae, 20 Mycoplasma hominis, and 77 Ureaplasma spp., and they were compared to fluoroquinolones, tetracyclines, and macrolides. Nemonoxacin MICs (μg/ml) ranged from 0.03 to 0.25 for M. pneumoniae, 0.25 to 8 for M. hominis, and 0.06 to >16 for Ureaplasma spp., and all of the ranges are similar to those of fluoroquinolones. The activity of nemonoxacin against Mycoplasmas was not affected by resistance to macrolides in the strains tested, but it seems to have the same resistant mechanism as fluoroquinolones. In addition, minimum bactericidal concentrations (MBC) of nemonoxacin to M. pneumoniae were within two dilutions of the MIC values, indicating a bactericidal effect on M. pneumoniae. Nemonoxacin merits further study for treating infections caused by these organisms.